Surgery in drug use-associated infective endocarditis: long-term survival is negatively affected by recurrence. (30th December 2019) - Rohn, Vilem; Laca, Branislav; Horn, Milan; Vlk, Lukas; Antonova, Petra; Mosna, Frantisek
Abstract: : OBJECTIVES: The prevalence of infectious endocarditis (IE) in intravenous drug users (IDUs) is increasing, and the number of patients who need surgery is also rising. Relatively little is known about the short-term and long-term outcomes of these operations. METHODS: This study is a retrospective analysis of our institutional results, focussing on risk factors for perioperative death, major adverse events and long-term survival. A total of 50 of the 66 (75.75%) patients had postoperative follow-up, and the mean follow-up time was 53.9 ± 9.66 months. Patients were divided into 2 groups depending on whether they were having their first operation or were being reoperated for recurrent IE. RESULTS: From March 2006 to December 2015, a total of 158 patients underwent surgery for IE; 72 (45.6%) of them were identified as active IDUs. The operative mortality in IDUs was 8.33% (6 patients), with no significant difference between the 2 groups ( P = 0.6569). Survival rates at 1 year, at 3 years and at the end of follow-up were 92%, 72% and 64%, respectively. There was significantly worse survival of patients with recurrent IE (log-rank test, P = 0.03). CONCLUSIONS: Although the short-term results of operation for IE in IDUs are good, long-term outcomes are not satisfactory. The survival of patients with recurrence of IE caused by return to intravenous drug use is significantly worse.